Peningkatan Status Gizi Pada Balita dengan Pemberian Madu - Retno Widowati; Handayani Handayani; Mulyani Mulyani; Yani Suryani (STKIP Andi Matappa, 2020)
The aim of community service is to improve the nutritional status of nutrition children under five with honey, in the working area of Sukawali Health Center and Pakuhaji Health Center in Tangerang Regency, Banten Province. Community service was carried out on 20 severely wasted children aged more than two years to five years as participants. Children under five as participants previously confirmed by measuring weight and height or length. The honey provided was from the Apis dorsata honey bee colonies which were harvested in North Kalimantan. Each participant drank as much as 2.5 mL of honey every morning and evening for 28 days. On the 14th day and 28th day the participants were re-measured their body weight and height or length. The results showed on the 28th day there were 2 wasted participants and 18 possible risk of overweight. The results of community service showed that regular and long-term honey provision to children, significantly increase the status of nutrition.